FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENANGANAN SAMPAH RUMAH TANGGA DI DESA LANTASAN BARU KECAMATAN PATUMBAK KABUPATEN DELISERDANG - darmanto ginting; rio ferdi yuandra; Cerya Maya Sari Surbakti (Jurnal Penelitian Kesmasy, 2020)
Waste is something that is, not used, disliked, or something that is disposed of that originates from human activities and does not happen by itself. The purpose of this study to find out what factors influence the people of LantasanBaruVillage so that they dispose of any trash. The type of research used is descriptive research with a cross sectional approach, namely an analytic (survey) researcher. The sample of this researcher was 64 respondents using total sampling. The Data Analysis Conducted univariate and bivariate with chi square test between knowledge shows p value of 0.027 which means there is a relationship between knowledge and waste management. Based on the attitude of p value of 0.025 which means there is a relationship between attitude and handling of waste. Based on the action of p value of 0.049 which means there is a relationship between action and handling of waste. Based on education p value is 1,000 which means there is no relationship between education and waste management.Based on the work p value of 0.305 which means there is no relationship between work and waste handling. Based on participation p value of 0.031, which means that there is a relationship between participation and waste management. Based on the trash facility p value is 0.23 which means there is a relationship between the trash facility and waste handling. Handling household waste in order to prevent the occurrence of variouskinds of diseases from improper garbage handling, separating organic and inorganic household waste, adding self support and participation and providing garbage facilities in handling waste.